2018
DOI: 10.3389/fmicb.2018.01711
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Potential Virulence, and Genetic Diversity of Listeria monocytogenes Isolates From Edible Mushrooms in Chinese Markets

Abstract: Listeria monocytogenes, an intracellular foodborne pathogen, is capable of causing listeriosis, such as meningitis, meningoencephalitis, and abortion. In recent years, the occurrence of Listeria monocytogenes in edible mushroom products has been reported in several countries. There are no guidelines for qualitative and quantitative detection of L. monocytogenes in mushroom products in China. Therefore, this study aimed to investigate the prevalence and contamination level of L. monocytogenes in edible mushroom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 50 publications
2
31
1
Order By: Relevance
“…Most positive samples (90.5%) had less than 10 MPN/g, and only 3.9% of the samples had above 110 MPN/g, which were mainly chicken samples. These results were consistent with those of studies in other countries such as Poland (Modzelewska-Kapitula and Maj-Sobotka, 2014), Brazil (Ristori et al, 2014), and Ireland (Khen et al, 2015); similar results were also reported in China for other food items (Chen et al, 2018a,b), suggesting low levels of L. monocytogenes contamination in fresh food products. The low number of L. monocytogenes in most samples could still be problematic; being psychrotrophic, it may grow during the storage period.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Most positive samples (90.5%) had less than 10 MPN/g, and only 3.9% of the samples had above 110 MPN/g, which were mainly chicken samples. These results were consistent with those of studies in other countries such as Poland (Modzelewska-Kapitula and Maj-Sobotka, 2014), Brazil (Ristori et al, 2014), and Ireland (Khen et al, 2015); similar results were also reported in China for other food items (Chen et al, 2018a,b), suggesting low levels of L. monocytogenes contamination in fresh food products. The low number of L. monocytogenes in most samples could still be problematic; being psychrotrophic, it may grow during the storage period.…”
Section: Discussionsupporting
confidence: 91%
“…The llsX gene (listeriolysin S, representing LIPI-3), which encodes a haemolytic cytotoxic factor associated with the destruction of gut microbiota during infection, is mainly present in a subset of lineage I (Cotter et al, 2008; Quereda et al, 2017a,b). LIPI-3 has been detected in several sequence types (STs) of L. monocytogenes strains, including ST1, ST3, ST4, ST6, ST77, ST79, ST191, ST213, ST217, ST224, ST288, ST363, ST380, ST382, ST389, ST489, ST554, ST581, ST619, ST778, ST999, ST1000, and ST1001 (Chen et al, 2018b; Kim et al, 2018; Wang et al, 2018). Furthermore, a cellobiose-family phosphotransferase system with a cluster of six genes was recently identified as LIPI-4 (Maury et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Many people in China consume a variety of edible mushrooms daily (28) . Mushrooms contain many nutritional components such as polyphenols, vitamins, minerals, fibres and polysaccharides (29) .…”
Section: Discussionmentioning
confidence: 99%
“…Eight isolates (11.11%) carried the llsX gene and mainly belonged to ST1, ST3, ST308, ST323, ST330, and ST619, whereas 15 isolates belonging to ST87 showed the presence of LIPI-4 in this study. LIPI-3 were mainly present in lineage I, included 21 STs belongs to 18 CCs (CC1, CC3, CC4, CC6, CC191, CC213, CC217, CC224, CC288, CC363, CC379, CC382 CC389, CC489, CC554, CC581, CC1000, and CC380) ( Chen et al, 2018 ; Hilliard et al, 2018 ; Kim et al, 2018 ; Wang et al, 2018 ). While LIPI-4 were only reported in CC4 isolates by Maury et al (2016) , recent studies reported that LIPI-4 presented in several other lineage I CCs and in a single lineage III CC in China, the United States, and Ireland, namely ST4, ST87, ST213, ST217, ST363, ST382, ST388, ST663, ST1002, ST1166, and ST619 ( Chen et al, 2018 ; Hilliard et al, 2018 ; Kim et al, 2018 ; Wang et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“… Maury et al (2016) identified that a cluster of six genes annotated as the cellobiose-family phosphotransferase system (PTS) and designated as LIPI-4, was highly associated with L. monocytogenes neuroinvasiveness and human maternal-neonatal (MN) infection. At present, LIPI-3 were found only in lineage I clonal complexes, 23 STs were found to carried LIPI-3 (ST1, ST1001, ST3, ST4, ST6, ST191, ST213, ST217, ST224, ST288, ST363, ST79, ST77, ST382, ST389, ST489, ST999, ST554, ST581, ST1000, ST380, ST778, and ST619), LIPI-4 presented in 11 STs belongs to lineage I and a single lineage III (ST4, ST87, ST213, ST217, ST363, ST382, ST388, ST663, ST1002, ST1166, and ST619) ( Chen et al, 2018 ; Kim et al, 2018 ; Wang et al, 2018 ). The presence of these virulence genes may be an important determinant to their pathogenicity.…”
Section: Introductionmentioning
confidence: 99%